Zircon Concentrate Enrichment by Dry Magnetic Separation and Centrifugal Air Separation; Minerals; Vol. 13, iss. 3 - Sachkov V. I. Viktor Ivanovich; Nefedov R. A. Roman Andreevich; Medvedev R. O. Rodion Olegovych; Amelichkin I. V. Ivan Vyacheslavovich; Sachkova A. S. Anna Sergeevna; Shcherbakov P. S. Pavel Sergeevich; Solovyev V. S. Vladislav Sergeevich; Leonov D. I. Daniil Igorevich; Biryukov D. A. Danil Aleksandrovich (2023, 2023)
Title screen